An efficient bit-loading algorithm for DMT applications - Sonalkar, R.V.; Shively, R.R. (IEEE communications letters, 2000)
This letter describes an efficient bit allocation algorithm for digital subscriber loop modems that use discrete multi-tone technology. The algorithm computes the optimum bit allocation profile within all constraints and requires fewer computations than the conventional "water-filling" approach. Conventional algorithms are unable to assign data bits to higher frequency bins over long loops with high level of interference due to the power spectrum mask limitation, even if the total power budget is not expended. We propose a novel scheme to distribute data over multiple bins at correspondingly reduced power in these, otherwise unpopulated bins.